Mapping the Digital Transformation of Education in Indonesia from 2012 to early 2025: A Bibliometric Analysis of Scopus-Indexed Publications - Fuadiy, Moch. Rizal; Rozi, M. Asep Fathur; Arafah, Nawal Nur; Kamal, Lahij; Sunoko, Ahmad (Journal of Educational Research and Practice, 2025)
The digital transformation of education in Indonesia has accelerated significantly, particularly after the COVID-19 pandemic. National initiatives like Merdeka Belajar have emphasized digital integration in teaching and learning, prompting scholarly interest in e-learning, online pedagogy, and technology-enhanced instruction. Despite this growing body of literature, there remains a lack of systematic analysis regarding how this research has evolved, which themes have dominated, and how collaboration networks have developed. This study aims to map the research landscape of digital education in Indonesia by conducting a bibliometric analysis of Scopus-indexed journal articles published between January, 1, 2012 and May, 31, 2025. Using the Biblioshiny interface of the R-based Bibliometrix package, 1,131 articles were analyzed to examine publication trends, thematic patterns, prominent keywords, top contributing authors and institutions, and the evolution of co-authorship networks. The results show a notable increase in publication volume beginning in 2020, coinciding with the national shift to online learning. Key research themes include "e-learning", "online learning", and "blended learning", while emerging topics such as "digital literacy", "gamification", and "student engagement" reflect new pedagogical directions. Leading institutions include Universitas Negeri Malang, Universitas Pendidikan Indonesia, and Universitas Negeri Yogyakarta, with collaboration patterns showing modest but growing international engagement. This study offers a comprehensive overview of how digital transformation has been addressed in Indonesian educational research and provides insights into its future trajectory. The findings serve as a reference for researchers, educators, and policymakers in identifying research gaps and shaping strategic directions for digital education.